1 H NMR‐based metabolomics study for identifying urinary biomarkers and perturbed metabolic pathways associated with severity of IgA nephropathy: a pilot study†. (2nd March 2017) - Kalantari, Shiva; Nafar, Mohsen; Samavat, Shiva; Parvin, Mahmoud
Abstract : The severity of IgA nephropathy (IgAN), the most common primary glomerulonephritis, is judged on the basis of histologic and clinical features. A limited number of studies have considered molecular signature of IgAN for this issue, and no reliable biomarkers have been presented non‐invasively for use in patient evaluations. This study aims to identify metabolite markers excreted in the urine and impaired pathways that are associated with a known marker of severity (proteinuria) to predict mild and severe stages of IgAN. Urine samples were analysed using nuclear magnetic resonance from biopsy‐proven IgAN patients at mild and severe stages. Multivariate statistical analysis and pathway analysis were performed. The most changed metabolites were acetoacetate, hypotaurine, homocysteine, L‐kynurenine and phenylalanine. Nine metabolites were positively correlated with proteinuria, including mesaconic acid, trans‐cinnamic acid, fumaric acid, 5‐thymidylic acid, anthranilic acid, indole, deoxyguanosine triphosphate, 13‐cis‐retinoic acid and nicotinamide riboside, while three metabolites were negatively correlated with proteinuria including acetoacetate, hypotaurine and hexanal. 'Phenylalanine metabolism' was the most significant pathway which was impaired in severe stage in comparison to mild stage of IgAN. This study indicates that nuclear magnetic resonance is a versatile technique that is capable of detecting metabolite biomarkers in combination with advanced multivariate statistical analysis. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : 1H NMR‐based metabolomics results of severe and mild stages of IgA nephropathy were analyzed with multivariate statistical analysis (OPLS‐DA). Predictive model revealed decreased urinary excretion of acetoacetate, hypotaurine, homocysteine, and L‐kynurenine and increased excretion of phenylalanine in severe stages in comparison with mild stage of IgA nephropathy. Important metabolic pathways in progression of IgA nephropathy were introduced based on significant differential metabolites.